Ho Xuan Huong’s Nom Poetry and Its Significance to the Current Issues of Gender Equality - Van, Vu Hong (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
Ho Xuan Huong was a famous Vietnamese poet who lived in the late 18th and early 19th centuries. She left behind many unique poems with a poetic style that is both thanh (right and pur vulgar) or tục (vulgar and dirty) and was dubbed “the Queen of Nom Poetry”. While nom poetry is a genre of poetry passed down from generation to generation without original text, Huong is considered one of the unique poets of Vietnamese literature. Many of her works have been lost; up to now, her poems still in circulation are mainly oral Nom poems. Her poetic system focuses primarily on promoting the role of women under the harsh regime of the feudal dynasty which is expressed to honor women while mocking and pointing out the negative aspects of the regime of “trọng nam khinh nữ